2. PILKADA LANGSUNG DAN REKONSTRUKSI DEMOKRASI INDONESIA - Manar, Dzunuwanus Ghulam (FORUM, 2014)
Election, either local or national sometimes can be assessed to mark success story of democracy in a community. However, people might not understand that election is only subsystem within democracy. There are many other subsystems that support democracy, such as policy, leadership, procedures and mechanisme, transparancy and accountability. In order to mark succesful democracy, people must consider any other factors that creates democratic system as a whole.